Significados atribuídos à paternidade por mulheres chefes de família de periferia urbana - Cúnico, Sabrina Daiana (2014)
Several are the transformations that the family has going through, situations that also implied in changes in the performance of parental roles. Whereas motherhood has many of its assumptions well naturalized, the paternity, supposedly, was the one what has most changed into the familiar scenery. In this context, the research from which originates the present dissertation had as the main goal to understand the meanings attributed to paternity by women heads of household in urban periphery. For this, an exploratory qualitative study was performed in a group of ten women, mothers, who constituted a monoparental family and that lived in an urban periphery from a countryside city located in Rio Grande do Sul State, Brazil. The number of participants followed the definition of the saturation criterion. The data collection instruments used were the semi-structured interviews and the focus group, with the data obtained processed by the analysis of thematic content. The results of this research are presented and discussed in three articles that compose this dissertation. Thus, the results of the first article pointed out to the existence of traditional and contemporary conceptions regarding to the structure of the family, as well as the role that the father has within the family. The second article, on the other hand, referred to a discussion about the importance of the pregnancy being part of project shared by the couple, especially by highlighting that many relationships end, even before the birth of the child, a situation which contributes to the difficulty of many fathers in establish their affective position toward these children. The results of the third article showed the existence of a number of crossings situations that pervade the coparental relationship after the couple's separation. Furthermore, it was noticed that the participant´s understanding regarding to the parental roles seem to have been permeated by the belief that the mother is naturally better prepared to take care of the children, while the father was delegated to a peripheral function. The issue which appeared with more emphasis in this study was the coexistence of traditional and modern meanings regarding to the paternity. While the mothers reported that the father is the "foundation" of the house, the head of the family, many of them asserted their wish of a more attentive and affective former partner with their children, showing signs of what is called "contemporary father", in the speech of women heads of households in urban periphery.